MASS CYTOMETRY ANALYSIS OF CROHN'S DISEASE-LIKE PHENOTYPE OF THE ILEOANAL POUCH FOLLOWING ILEAL POUCH-ANAL ANASTOMOSIS FOR ULCERATIVE COLITIS. (22nd January 2022) - Cao, Siyan; Cella, Marina; Jaeger, Natalia; Ciorba, Matthew; Escudero, Guadalupe Oliva; Gutierrez, Alexandra; Rood, Richard; Rubin, Deborah; Deepak, Parakkal; Colonna, Marco
Abstract: BACKGROUNDS: For patients with medically refractory ulcerative colitis (UC), total proctocolectomy and ileal pouch-anal anastomosis (IPAA) has been the definitive surgery of choice. Approximately 10% of patients who were initially diagnosed with UC and underwent an IPAA, subsequently develop a condition referred to as Crohn's disease-like phenotype of ileoanal pouch (CDP). CDP is typified by ulcers in the pre-pouch ileum, stricture involving the pouch or pre-pouch ileum, and/or fistulas. The etiology of CDP remains unknown and remains difficult to diagnose and treat. To define the mucosal immunology of CDP, we analyzed ileal samples from patients with CDP and patients with a normal pouch and pre-pouch ileum using mass cytometry (CyTOF). METHODS: Ileal mucosal biopsies from patients with a history of CDP with long-segmental pre-pouch ileitis (n=10) and those with a normal pouch and pre-pouch ileum after IPAA for UC (n=9) were collected during routine pouchoscopy, frozen in medium, and processed, barcoded and analyzed in one CyTOF experiment. Data were analyzed by using viSNE for dimensionality reduction and CITRUS for clustering in Cytobank. RESULTS: Compared with patients with a normal pouch/ileum, we observed the following in ileal samples from CDP based on viSNE analysis (Figure 1): 1) A decreased abundance of CD8+CD103+ tissue-resident T cells (TRM). This result is similar to data from colonic mucosal samples in patients with UC (our internal data not shown here and others), but unlike data from prior studies derived from inflamed ileal mucosal specimens in patients with CD (native bowel anatomy without IPAA) which had increased CD8+ TRM. 2) An increase in CD4+CD103-CD161+ Th17 cells previously linked to an activated Th17 phenotype in Crohn's disease specimens. 3) Increased CD4+CD103-CD45RA+ T cells associated with reduced IL-10/IL-4 and increased TNF-a in IBD. 4) A higher abundance of CD4+CD103-TIGIT+ T cells that were previously shown to predict severity of pediatric IBD. 5) A decrease in CD8+CD103+CD127+ TRM in CDP, although its role in IBD is unclear. The findings from viSNE were confirmed by CITRUS (Figure 2). Further analyses of pouch samples as well as ileal samples from UC and CD with native GI anatomy (for comparison) using CyTOF and scRNAseq are currently underway. CONCLUSIONS: We used mass cytometry to identify immune cells specific to ileal mucosa from patients with CDP. Interestingly, immune cells from the inflamed pre-pouch ileum share some features of those from either UC or CD with native bowel anatomy. We also identified an altered immune cell population which appears to be specific to CDP. These data reveal a unique immune landscape of CDP which may serve as a foundation for identifying therapeutic approaches that target specific cell populations for medical management of CDP.